On Properties of Differences Polynomials about Meromorphic Functions - Jianming Qi; Jie Ding; Wenjun Yuan (Discrete Dynamics in Nature and Society)
We study the value distribution of a special class difference polynomial about finite order meromorphic function. Our methods of the proof are also different from ones in the previous results by Chen (2011), Liu and Laine (2010), and Liu and Yang (2009).